Age as a key risk factor for deep vein thrombosis in patients with lower limb cellulitis - Romane Teshima; Natsuko Saito-Sasaki; Yu Sawada (Frontiers in Medicine)
BackgroundCellulitis of the lower extremities is a common bacterial skin infection that can lead to various complications, including deep vein thrombosis (DVT). Although previous studies have suggested an increased risk of thrombosis due to the pro-inflammatory state induced by cellulitis, the specific clinical characteristics and risk factors associated with DVT in cellulitis patients remain poorly understood. This study aims to identify the clinical characteristics and risk factors for DVT in patients with lower limb cellulitis.MethodsWe conducted a 10-year retrospective study of patients treated for lower limb cellulitis at our institution between January 2013 and December 2023. Patients who underwent ultrasound examination to assess for DVT were included in the analysis. Clinical data were collected, including age, D-dimer levels, C-reactive protein (CRP) levels, body mass index (BMI), duration of antibiotic treatment, and relevant medical history (e.g., diabetes, malignancy, the use of corticosteroids, and immunosuppressive agents). Statistical analyses were performed to identify risk factors for thrombosis.ResultsAmong the patients included in the study, those who developed DVT were significantly older, with the majority being 70 years or older. No significant associations were found between thrombosis and other clinical parameters, including elevated CRP levels, D-dimer levels, BMI, or the duration of antibiotic treatment. Additionally, neither diabetes nor the use of corticosteroids or immunosuppressants showed a significant correlation with DVT development. Importantly, thrombosis occurred in both the affected and non-affected limbs, with no significant difference between them.ConclusionAge, particularly being 70 years or older, was identified as an independent risk factor for the development of DVT in patients with lower limb cellulitis. These findings suggest that advanced age plays a critical role in DVT development in cellulitis patients, and further investigation is needed to explore the underlying mechanisms.